2013
DOI: 10.2136/sh12-08-0025
|View full text |Cite
|
Sign up to set email alerts
|

Forty Years of Soil Formation in a South Georgia, USA Borrow Pit

Abstract: This study investigated soil properties in a sand borrow pit in southern Georgia, USA that was used in 1961 and then abandoned with no efforts at reclamation and compares those developing soils to natural soils surrounding the pit. There are distinct vegetative zones within the pit; three are included in this study. Soil samples were collected and described using standard techniques and analyzed for bulk density, C content, texture, pH, and penetration resistance. Piezometers and thermometers were installed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 59 publications
0
39
0
Order By: Relevance
“…Conversely, studies carried out on archaeological structures have been useful in soil research. Parsons et al (1962) used soils formed in dated archaeological features to estimate rates of soil formation, while archaeological sites (Sandor and Eash, 1991) and features (Brevik and Fenton, 2012;Brevik, 2013b) (Fig. 4) have been used to investigate long-term effects of human activity on soil processes and properties.…”
Section: Soils and Social Sciencesmentioning
confidence: 99%
“…Conversely, studies carried out on archaeological structures have been useful in soil research. Parsons et al (1962) used soils formed in dated archaeological features to estimate rates of soil formation, while archaeological sites (Sandor and Eash, 1991) and features (Brevik and Fenton, 2012;Brevik, 2013b) (Fig. 4) have been used to investigate long-term effects of human activity on soil processes and properties.…”
Section: Soils and Social Sciencesmentioning
confidence: 99%
“…This is why changes in soil management results in changes in the quality of the wine and in the quantity of grapes (Ruiz-Colmenero et al, 2011, 2013, and farmers have their own perceptions about how no-tillage damages the quality of the wine (Marqués et al, 2015). Sustainably managed soils can increase soil aggregate stability, water retention, and biodiversity and reduce soil and nutrient losses (Costantini et al, 2015;Ola et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Vineyards often have highly degraded soils, with soil lowering up to 0.5 to 2 mm yr À1 Prosdocimi et al, 2016a), rates that vastly exceed natural rates of pedogenesis (Brevik, 2013), which is due to: i) traditional tillage management (Cerdan et al, 2010;Francone et al, 2010); ii) the application of pesticides (Marín et al, 2016); iii) low soil organic matter and water retention capacity (Brillante et al, 2015); iv) biological degradation (Costantini et al, 2015;Cagnarli et al, 2015); and, v) the impact of irrigation (Terrón et al, 2015). Most of the wine growers, local and regional governments, and viticulture companies have contributed to improve the production of wine, dissemination of tourism, promotion of vineyard landscapes.…”
Section: Introductionmentioning
confidence: 99%
“…Although the impact of topographic position on soil properties on SOC content is widely recognized (Venterea et al, 2003;Fu et al, 2004;Brevik, 2013), relatively few studies have been conducted to examine the role of topographic position (Fernández-Romero et al, 2014;Lozano-García et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The spatial variation of soil properties may also be significantly influenced by aspect (which may induce microclimate variations), physiography, parent material, and L. Parras-Alcántara et al: Soil organic carbon along an altitudinal gradient vegetation (López-Vicente et al, 2009;Brevik, 2013;Ashley et al, 2014;Bakhshandeh et al, 2014;Dingil et al, 2014;Gebrelibanos et al, 2014;Kirkpatrick et al, 2014). Ovales and Collins (1986) evaluated soil variability due to pedogenic processes across landscapes in contrasting climatic environments and concluded that topographic position and variations in soil properties were significantly related.…”
Section: Introductionmentioning
confidence: 99%